Family centred neonatal palliative care in children's hospices: A qualitative study of parents' experiences. Issue 2 (April 2021) - Mendizabal-Espinosa, Rosa Maria; Price, Jayne E.
Abstract: Since 1982, children's hospices in the UK have provided services where families can care for their children at the end of life (EOL) in a less medicalised environment. More recently, the services of many children's hospices have extended to newborn babies and their families. This paper explores the experiences of three families (five parents) who availed of children's hospices services when their babies required a palliative approach to care. Early diagnosis of a life-limiting condition in pregnancy allowed advanced care planning and enabled parental participation in decision-making before birth. A homely environment, as well as constant support and a sensitive approach from expert staff encouraged parental involvement in all aspects of their baby's care whilst in hospice. Extended time with their baby after death enabled parents to feel connected with their infant. The holistic and family-centred approach to care from children's hospices is highly valued by parents of newborn babies.